Association of heat shock protein 70 gene polymorphisms with acute thermal tolerance, growth, and egg production traits of native chickens in Taiwan - H.-M. Liang; D.-Y. Lin; Y.-D. Hsuuw; T.-P. Huang; H.-L. Chang; C.-Y. Lin; H.-H. Wu; K.-H. Hung (Archives Animal Breeding, 2016)
Heat stress is among the most challenging environmental conditions affecting commercial poultry. It severely affects growth and egg production, particularly in tropical and subtropical regions. This study aimed to examine physiological responses – including triiodothyronine (T3) levels, enzymatic activity of creatine kinase (CK) and lactate dehydrogenase (LDH), respiratory rates, and cloacal temperature – to acute heat stress associated with different genotypes of the HSP70 gene and to evaluate the association of these polymorphisms with growth and egg production. Genotyping was performed by single-strand conformation polymorphism analysis. The polymorphisms identified were A258A, A258G, and G258G. Twenty 12-week old birds were randomly selected from each genotype and exposed to 40 °C ambient temperature for 1 h. Blood samples were collected at 0 and 1 h following heat stress. Respiratory rate and cloacal temperature were measured following 0, 30, and 60 min of exposure. After 1 h, the A258A genotype exhibited lower levels of CK activity and plasma T3. Neither respiratory rate nor cloacal temperature displayed a significant association with the genotypes. Body weight gain differed among the genotypes for males (F =  3.268, P = 0.041) and females (F =  14.029, P < 0.001), and the A258A genotype exhibited the greatest weight gain at 0–16 weeks of age for both genders. There were no significant differences among genotypes regarding egg weight at first egg or the number of eggs laid until 40 weeks of age. The A258A genotype displayed higher heat tolerance with no negative effects on growth performance and egg production.